The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.5433/1679-0367.2021v42n1p3
|View full text |Cite
|
Sign up to set email alerts
|

Malacofauna bentônica do Lago Igapó, Londrina (Paraná, Brasil), com ênfase na espécie invasora mexilhão-dourado Limnoperna fortunei (Dunker, 1857)

Abstract: Objetivo: quantificar a abundância e a biomassa de moluscos bentônicos no Lago Igapó I, Londrina, Paraná, Brasil. Material e Métodos: foram realizadas duas coletas no Lago Igapó I, a primeira em junho de 2015 e a segunda em fevereiro de 2016. O substrato (incluindo os moluscos incrustados) foi amostrado utilizando um quadrante com área de 1 m2, onde 10 amostragens foram realizadas entre três pontos distintos do lago. Os moluscos capturados foram anestesiados e eutanasiados por superexposição ao gelo. Posterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…On the other hand, Duchini et al (2018) indicated that areas with L. fortunei favor the proliferation of other invertebrates (even gastropods), but without concluding whether this result increases or decreases their diversity. Instead, Ferraz et al (2021) indicated for some lakes in southern Brazil that the presence of L. fortunei has been positive in non-native species, while negative in native species.…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, Duchini et al (2018) indicated that areas with L. fortunei favor the proliferation of other invertebrates (even gastropods), but without concluding whether this result increases or decreases their diversity. Instead, Ferraz et al (2021) indicated for some lakes in southern Brazil that the presence of L. fortunei has been positive in non-native species, while negative in native species.…”
Section: Introductionmentioning
confidence: 96%